To TTP or not to TTP? Exploiting TTPs to improve ML-based malware detection - Sharma, Y; Giunchiglia, E; Birnbach, S; Martinovic, I (IEEE, 2023)
In the last decade, machine learning (ML) methods have increasingly been applied to the task of malware detection. While these approaches have surely demonstrated their effectiveness, they still present limitations, some of which are a consequence of their purely data-driven nature. In this paper, we show how the MITRE ATT&CK framework of tactics, techniques, and procedures (TTPs) can be exploited to overcome such limitations and improve their ability to detect malware on networks. We conduct an extensive experimental analysis, testing 7 ML models on 5 large datasets comprising over 37 million flows. Our results clearly demonstrate that adding TTP-based features for training the models robustly improves their performance. Our models outperform the standard ones 922 times out of a total of 952, (i.e., 96.8% of the time), with the biggest improvements (up to 84.9% in terms of FPR) being observed in situations designed to be challenging for ML models.